2020
DOI: 10.1021/acsomega.0c00278
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Failure Mechanisms in Brittle Shales

Abstract: The brittle failure of Chengkou shale occurs throughout the exploration and development processes of hydrocarbons. To investigate the failure mechanisms of Chengkou shale and analyze the associated mechanical behavior such as crack initiation, propagation, and coalescence at different stress levels, a series of laboratory experiments were conducted on servo-controlled triaxial cells equipped with ultrasound monitoring. The experimental results show that key mechanical parameters such as peak stress σ p , stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The fracture conductivity of igneous rocks is strong, and the pressure penetration of the drilling fluid along the fracture further affects wellbore stability. 18 , 19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fracture conductivity of igneous rocks is strong, and the pressure penetration of the drilling fluid along the fracture further affects wellbore stability. 18 , 19 …”
Section: Resultsmentioning
confidence: 99%
“…The fractures in igneous rocks are relatively developed, and the mechanical weak plane effect of the fractures is the main factor affecting borehole wall collapse. The fracture conductivity of igneous rocks is strong, and the pressure penetration of the drilling fluid along the fracture further affects wellbore stability. , …”
Section: Resultsmentioning
confidence: 99%
“…The mechanical failure of different formation rocks such as sandstones, limestones, and shales has been extensively investigated in the literature. Although the mechanical failure of formation can be successfully estimated, a set of information is required for the prediction of geomechanical properties to understand the behavior of a reservoir rock system. Poisson’s ratio, shear modulus, Young’s modulus, stress intensity factor, and all related formation stress parameters are required to be evaluated to predict the behavior and failure of a reservoir rock. This can be a long and costly experimental process requiring complex equipment.…”
Section: Introductionmentioning
confidence: 99%
“… 1 4 It has been reported that China has approximately 36 trillion cubic meters of recoverable shale gas resources and has made an ambitious plan for large-scale gas extraction. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…The successful exploitation of unconventional oil and gas resources (e.g., shale gas) in North America has inspired an energy revolution because of a rapid increase in energy demand on a worldwide scale. It has been reported that China has approximately 36 trillion cubic meters of recoverable shale gas resources and has made an ambitious plan for large-scale gas extraction. , …”
Section: Introductionmentioning
confidence: 99%